REVISTA SENHOR: MODERNIDADE E CULTURA NA IMPRENSA BRASILEIRA - Basso, Eliane Fátima Corti (2005)
Magazine Sir: modernity and culture in the Brazilian press it has as objective to rescue the history of a publication that marked time. Produced in the period of 1959 the 1964, the magazine demonstrated its paper as a central space of quarrel of cultural subjects. Fruit of a specific conjuncture, Sir behaved itself as an encyclopedia of 50 years and beginning of years 60, divulging, in the set of news articles that produced, chronicles, assays, critical and articles, the values and the effective cultural movements, many times expressing new forms of behavior, considered advanced then. The used methodology in the research is of the descriptive analysis and qualitative of the content of the published substances and the theoretical approach it is based on the estimated ones of the interdisciplinaridade of the chain of the Cultural Studies. The conclusions had pointed the characterization of the magazine as a publication that translates Cultural the Journalism formative, come back the intellectualized people or multiplying calls of opinion, showing as one of the most important considered magazines "cultured" of the Brazilian market. It was a magazine directed predominantly for a culturally elitizado masculine public and/or economically. The idea is still conceived of that SIR, for its graphical and publishing project, was in the vanguard of Brazilian publications of all the times.